Online Learning Program Evaluation to Improve the Education Quality in Primary School - Sintha Wahjusaputri; Faariq Robiith Al Khuwarizmi; Dwi Priyono (STAI Hubbulwathan Duri, 2021)
This research aims to measure the effectiveness of online learning programs during the COVID-19 pandemic in improving the quality of education at one of the Islamic School in Jakarta. This study uses a qualitative descriptive method and a discrepancy evaluation model (DEM). The evaluation model was chosen to see the gap between standards and implementation in the field. These aspects include six stages of inequality evaluation, online learning principles, student learning outcomes, and characteristics of the quality of education. School management must always carry out strict supervision and monitoring so that online learning can run smoothly and effectively to minimize the possibility of gaps and achieve all the characteristics contained in the implementation standards. The results of this evaluation relate to the quality of education at Islamic schools.